THE INFLUENCE OF THE INDEPENDENT BOARD OF COMMISSIONERS, AUDIT COMMITTEES, AND AUDIT QUALITY ON TAX AVOIDANCE - Wulandari, Yuyun Hardika; Najihah, Naila (Reinforce: Journal of Sharia Management, 2025)
This study aims to analyze the effects of an independent board of commissioners, an the audit committee, and audit quality on tax avoidance in consumer goods companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. A quantitative approach was employed using multiple linear regression in EViews. The sample comprised 93 companies selected through purposive sampling. Partial test results showed that the audit committee had a significant negative effect on tax avoidance (p = 0.048 < 0.05), while the independent board of commissioners (p = 0.279 > 0.05) and audit quality (p = 0.187 > 0.05) had no significant effect. The simultaneous test (F-test) indicated that the three variables collectively did not significantly influence tax avoidance (sig = 0.456 > 0.05). The coefficient of determination (R²) was 0.011, indicating that the model explained only 1.1% of the variation in tax avoidance, with the remaining variation influenced by variables outside the model. These findings underscore the importance of strengthening the audit committee's oversight of corporate tax practices, while further studies are needed to examine the impact of other internal and external governance factors.